Expansion of Coccidioidomycosis Endemic Regions in the United States in Response to Climate Change. Issue 10 (10th October 2019) - Gorris, Morgan E.; Treseder, Kathleen K.; Zender, Charles S.; Randerson, James T.
Abstract: Coccidioidomycosis (Valley fever) is a fungal disease endemic to the southwestern United States. Across this region, temperature and precipitation influence the extent of the endemic region and number of Valley fever cases. Climate projections for the western United States indicate that temperatures will increase and precipitation patterns will shift, which may alter disease dynamics. We estimated the area potentially endemic to Valley fever using a climate niche model derived from contemporary climate and disease incidence data. We then used our model with projections of climate from Earth system models to assess how endemic areas will change during the 21st century. By 2100 in a high warming scenario, our model predicts that the area of climate‐limited endemicity will more than double, the number of affected states will increase from 12 to 17, and the number of Valley fever cases will increase by 50%. The Valley fever endemic region will expand north into dry western states, including Idaho, Wyoming, Montana, Nebraska, South Dakota, and North Dakota. Precipitation will limit the disease from spreading into states farther east and along the central and northern Pacific coast. This is the first quantitative estimate of how climate change may influence Valley fever in the United States. Our predictive model of Valley fever endemicity may provide guidance to public health officials to establish disease surveillance programs and design mitigation efforts to limit the impacts of this disease. Plain Language Summary: Valley fever is a fungal disease most common in the southwestern United States. Generally, the disease is limited to areas that are hot and dry. Climate change will cause the western United States to become hotter and may change the location, timing, and amount of rain. This is likely to change which counties are affected by Valley fever. We used climate observations to estimate which counties in the United States have a higher risk for Valley fever. Then, we used predictions of future climate to map which counties may become affected by Valley fever during the remainder of the 21st century. By 2100, our model predicts that the area affected by Valley fever will more than double and the number of people who become sick will increase by 50%. The area affected by Valley fever will expand north into drier states in the western US, including Idaho, Wyoming, Montana, Nebraska, South Dakota, and North Dakota. Our estimate may help public health officials develop more effective plans so less people suffer from this disease. Key Points: We created a niche model to estimate climate limits on the spatial extent of Valley fever endemicity in the United States For a high warming scenario, the area of climate‐limited endemicity will more than double by 2100, expanding northward into dry western states Our predictive model of Valley fever endemic regions may help mitigate disease impacts as the disease spreads into new regions